EPIDEMIOLOGIC STUDY OF OPHTHALMIA NEONATORUM AND IMPACT OF PROPHYLAXIS ON ITS INCIDENCE - M. Ghahramani A. A. Ghahramani (Acta Medica Iranica, 2007)
Prevention of ophthalmia neonatorum (ON) in the delivery room has been recommended by the Iranian Ministry of Health and Medical Education only if the mother is affected by STDs. This study aimed at finding out whether the neonatal wards should do prophylaxis as recommended or it is necessary to revise the previously-related protocols. In a randomized clinical trial, 130 full-term neonates born vaginally were selected on simple method in a period of three months and were divided randomly into control and case groups in such a way to be compatible regarding weight, gestational age, and sex. After obtaining parents' permission, 0.5% erythromycin ointment was used for ON prophylaxis. All the newborns were then examined regarding the presence of conjunctivitis during the third and the tenth day of life. The results showed that totally 8 newborns were affected with conjunctivitis, 7 of whom (87.5%) belonged to the control group and 1 to the case group (12.5%). However, this difference was not significant. This finding might be due to the inadequate frequency of affected subjects in comparison to the whole subjects under study. Considering other studies showing significant effect of drugs used in ON prophylaxis (silver nitrate, tetracycline, erythromycin, povidone-iodine) and based on the results of this study, it is highly recommended that neonatal wards of hospitals in our country carry out prophylaxis of ON in all subjects.